Investigation of electron irradiation induced-changes in poly(vinylidene fluoride) films - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Dahlan, Khairul Zaman M. (Elsevier Science, 2002)
The radiation-induced changes taking place in poly(vinylidene fluoride) (PVDF) films exposed to electron irradiation were investigated in correlation with the applied doses. Samples were irradiated in air at room temperature by a universal electron beam accelerator to doses in the range of 100-1200 kGy. Various properties of the irradiated PVDF films were studied using FTIR, differential scanning calorimetry (DSC) and universal mechanical tester. Unirradiated PVDF film was used as a reference. Electron irradiation was found to induce changes in physical, chemical, thermal, structural and mechanical properties of PVDF films and such changes vary depending on the irradiation dose.